ANALISA LAPORAN KEUANGAN PT. PLN (PERSERO) CABANG PALEMBANG RAYON RIVAI SEBAGAI DASAR UNTUK MENILAI KONDISI KINERJA MANAJEMEN - Titi Suelmi (JURNAL KOMPETITIF, 2013)
This research mainly discuss about financial ratios to be used as basis for decision making by the concerned parties of PLN Company. The objective of this research is to acquire companyÃ¢â‚¬â„¢s finantial ratios in order to evaluate management performance which in turn will be used as decision making basis. Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â  After a thorough study, research shows that companyÃ¢â‚¬â„¢s liquidity ratio as a whole concluded as liquid, seen from the increase of PLN CompanyÃ¢â‚¬â„¢s laverage factor every year. Profitability ratio of PLN Company is categorized as healthy, and activity ratio shows a sign of healty company condition.Ã‚Â Key Word : management performance, Profitability ratio, activity ratio Ã‚Â